Preparation method and application of zinc negative electrode modified by bismuth sulfide-nitrogen-doped carbon composite interface layer

By preparing a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer on the surface of the zinc anode, the problems of dendrite growth and redox kinetics of the zinc anode were solved, and stable cycling and efficient charge-discharge of zinc-ion batteries were achieved.

CN122291374APending Publication Date: 2026-06-26CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610253856.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-03
Publication Date
2026-06-26

AI Technical Summary

Technical Problem

Zinc metal anodes in aqueous zinc-ion batteries suffer from problems such as hydrogen evolution reaction, corrosion, passivation, and dendrite growth, resulting in poor reversibility of zinc anodes, unstable battery cycle life, and even short-circuit failure.

Method used

Rod-shaped bismuth sulfide-nitrogen-doped carbon materials were prepared by a solvothermal method. A carbon layer was formed by polymerization of dopamine hydrochloride and used as an interface modification layer for zinc anodes to inhibit dendrite growth and improve redox kinetics.

Benefits of technology

It significantly improves zinc ion transport and redox reactions, enhances the coulombic efficiency and cycle stability of the zinc anode, extends battery life, reduces battery internal resistance and polarization, and improves charge and discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122291374A_ABST
    Figure CN122291374A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing and applying a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer modified zinc anode. First, bismuth nitrate pentahydrate and thioacetamide are mixed and subjected to a hydrothermal reaction to obtain bismuth sulfide powder. Then, a layer of polydopamine (PDA) is coated onto the surface of the bismuth sulfide using dopamine hydrochloride, followed by high-temperature annealing to decompose the PDA and generate nitrogen-doped carbon material. Finally, the bismuth sulfide-nitrogen-doped carbon (Bi2S3-NC) material is coated onto the surface of zinc foil using a coating tool to obtain a Bi2S3-NC interface layer modified zinc anode. This interface layer regulates zinc ion deposition and improves the problem of zinc dendrite growth. Furthermore, the Bi2S3-NC composite coating effectively improves the redox kinetics of zinc ions, increasing the coulombic efficiency of the zinc anode. Therefore, the prepared bismuth sulfide-nitrogen-doped carbon composite interface layer modified zinc anode symmetric cell exhibits superior cycle stability, a more stable coulombic efficiency in the half-cell, and a more outstanding capacity retention rate in the assembled full cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of anode material preparation technology, specifically relating to a method for preparing and applying a zinc anode modified with a bismuth sulfide-nitrogen-doped carbon composite interface layer. Background Technology

[0002] With the rapid depletion of fossil fuels and increasing public awareness of environmental protection, the development of advanced energy storage technologies to efficiently utilize renewable energy has become urgent. Lithium-ion batteries (LIBs) have achieved great success in the portable and smart device market due to their high energy density and long cycle life. Nevertheless, the large-scale application of LIBs in future electric vehicles and stationary energy storage grids still faces many challenges, such as limited lithium resources and safety issues arising from the use of flammable or explosive materials. Among numerous battery technologies, aqueous zinc-ion batteries (AZIBs) have attracted widespread attention due to their advantages such as high theoretical capacity (820 mAh / g), low redox potential (-0.76 V vs. SHE), non-toxicity, and abundant zinc reserves. However, zinc metal anodes suffer from a series of problems, such as hydrogen evolution reaction (HER), corrosion, passivation, and dendrite growth, leading to poor reversibility of the zinc anode, unstable battery cycle life, and even short-circuit failure. These problems severely hinder the practical application of aqueous zinc-ion batteries. To address the current problems with zinc anodes, researchers have proposed the following improvement methods: zinc anode structural design, electrolyte modification, separator modification, and zinc anode interface modification. Among these, the simplest and most effective method is the interface modification layer of the zinc anode. Previously reported interface modification layer materials include metals, inorganic salts, organic substances, and oxide coatings, all of which have shown some improvement effects on zinc anode problems.

[0003] However, these traditional interface modification layer materials still have some limitations in practical applications. For example, metal coatings may increase the cost and weight of the battery, and some metals may have stability issues in aqueous electrolytes; inorganic salt coatings have limited ionic conductivity and the ability to regulate zinc ion deposition; organic coatings have poor mechanical properties and thermal stability; and although oxide coatings have a certain degree of chemical stability, their effect on improving zinc ion redox kinetics is not ideal. Therefore, developing novel zinc anode materials remains an important means to solve the problems of zinc anodes and promote the rapid development of zinc-based batteries.

[0004] Currently, bismuth sulfide and carbon composite materials combine the advantages of both materials, exhibiting both high specific capacity and good conductivity. The combination of these two materials holds promise for further improving the performance of zinc-ion batteries. Therefore, this invention constructs a rod-shaped bismuth sulfide-nitrogen-doped carbon material as a zinc anode coating to address the problems existing in zinc anodes and improve the performance of zinc-ion batteries. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a method for preparing and applying a zinc anode modified with a bismuth sulfide-nitrogen-doped carbon composite interface layer. Rod-shaped bismuth sulfide is prepared using a solvothermal method, then coated with polydopamine synthesized from dopamine hydrochloride, followed by annealing to form a carbon layer coating. Bi₂S₃@NC is then coated onto the zinc surface using a coating method, inhibiting dendrite growth and improving redox kinetics. The interface modification layer, with its good ionic conductivity, significantly improves zinc ion transport. Therefore, the modified composite-coated zinc anode achieves more stable long-cycle operation.

[0006] To achieve the above objectives, the present invention provides a zinc anode modified with a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer, comprising a zinc substrate and a Bi2S3@NC interface modification layer coated on its surface.

[0007] A rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer modified zinc anode includes a zinc substrate and a bismuth sulfide-nitrogen-doped carbon interface modification layer coated on its surface.

[0008] A method for preparing a zinc anode modified with a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer includes the following steps:

[0009] (1) Add bismuth nitrate pentahydrate and thioacetamide to deionized water, and then add concentrated hydrochloric acid to obtain a mixed solution; (2) After stirring the mixed solution, the reaction was carried out. After filtration, a black product was obtained. It was washed with deionized water and ethanol once, dried, and then cooled to ambient temperature to obtain Bi2S3. (3) Bi2S3 and dopamine hydrochloride were ultrasonically dispersed in a trihydroxyaminomethane buffer solution, allowing dopamine hydrochloride to polymerize and coat the surface of Bi2S3 with polydopamine. The mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain the precipitate. (4) The above precipitate was calcined in a nitrogen atmosphere to finally obtain Bi2S3@NC material; (5) Mix and grind Bi2S3@NC, conductive carbon black and polyvinylidene fluoride (PVDF) and dissolve them in N-2-methylpyrrolidone (NMP). Use a four-sided coater to coat the slurry onto the zinc foil surface. After drying, the modified zinc anode material can be obtained.

[0010] Preferably, in step (1), the molar ratio of bismuth nitrate pentahydrate to thioacetamide is 1:(3-5), preferably 1:4, and the molar volume of bismuth nitrate pentahydrate, thioacetamide, deionized water, and concentrated hydrochloric acid is 1:(3-5):(40-60):(4-6) (mmol / mmol / mL / mL), preferably 1:4:50:5 (mmol / mmol / mL / mL).

[0011] Preferably, in step (2), the stirring is performed for 15-25 minutes at a speed of 480-600 rpm; preferably, the stirring is performed for 20 minutes at a speed of 500 rpm.

[0012] Preferably, in step (2), the reaction conditions are 130-150℃ for 10-14h, and more preferably, 140℃ for 12h.

[0013] Preferably, in step (3), the solid-liquid ratio of Bi2S3 and dopamine hydrochloride to trihydroxyaminomethane buffer solution is 1:1:(90-110) (g / g / mL), preferably 1:1:100 (g / g / mL), the concentration of trihydroxyaminomethane buffer solution is 8-12 mM, the ultrasonic dispersion conditions are 35-45 kHz, and the dispersion time is 10-15 h, preferably the concentration of trihydroxyaminomethane buffer solution is 10 mM, the ultrasonic dispersion conditions are 40 kHz, and the dispersion time is 12 h. In steps (2), (3), and (5), the drying conditions are vacuum drying at 75-90℃ for 10-14 hours, preferably vacuum drying at 80℃ for 12 hours.

[0014] Preferably, in step (4), the calcination temperature is 480-600℃, the calcination time is 3-5 h, and the heating rate is 1-3℃ / min. Preferably, the calcination temperature is 500℃, the calcination time is 4 h, and the heating rate is 2℃ / min.

[0015] In step (5), Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed, ground, and dissolved in N-2-methylpyrrolidone (NMP) in a ratio of 7:2:1. The mass ratio of Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride is (5-8):(1-3):1. Preferably, the mass ratio of Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride (PVDF) is 7:2:1. The concentration of the mixture of Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride (PVDF) in N-2-methylpyrrolidone (NMP) is 0.4-0.7 g / mL, preferably 0.5 g / mL.

[0016] Preferably, in step (5), the coating thickness of the four-sided coater is 5-50µm, preferably 20µm; The zinc foil mentioned in step (5) is a pre-treated zinc foil. The zinc foil pre-treatment steps are: placing the zinc foil in an organic solvent for ultrasonic cleaning, and then cutting and flattening the zinc foil; The organic solvent is ethanol or NMP, with a mass percentage ≥95%; the zinc foil is cut into small round pieces.

[0017] The zinc anode composed of bismuth sulfide-nitrogen-doped carbon material or the zinc anode composed of sulfide-carbon material prepared by the above method is used as an anode material in aqueous zinc-ion batteries.

[0018] Preferably, the zinc anode or the zinc anode obtained by the preparation method is used as the anode, the positive electrode material is Mn2V2O7, the electrolyte is an aqueous solution of zinc salt, and the separator is glass fiber.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The zinc anode modified with a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer proposed in this invention effectively overcomes the shortcomings of traditional interface modification layer materials. Rod-shaped bismuth sulfide possesses a unique crystal structure and electronic properties, providing abundant diffusion channels for zinc ions, which is beneficial for rapid transport and uniform deposition of zinc ions. Nitrogen-doped carbon materials not only exhibit good conductivity but also increase the specific surface area and active sites of the material, further promoting the redox reaction of zinc ions.

[0020] By combining bismuth sulfide and nitrogen-doped carbon materials to form an interface layer, a synergistic effect is achieved between the two. On the one hand, bismuth sulfide can serve as an active site for zinc ion deposition, guiding zinc ions to deposit uniformly on the zinc anode surface and inhibiting the growth of zinc dendrites. On the other hand, nitrogen-doped carbon materials can improve the conductivity and stability of the interface layer and improve the redox kinetics of zinc ions, thereby improving the coulombic efficiency and cycle stability of the zinc anode.

[0021] In practical applications, this novel zinc negative energy significantly improves the performance of aqueous zinc-ion batteries. For symmetrical batteries, it enables more stable charge-discharge cycles, reduces internal resistance and polarization, and extends battery life. For half-cells, it effectively improves coulombic efficiency and reduces energy loss. In full-cell assembly, it ensures higher capacity retention and better charge-discharge performance. Attached Figure Description

[0022] Figure 1 The zinc anodes prepared in Examples 1-4 and the zinc anodes prepared in Comparative Examples 1-3 were compared at 2 mA·cm⁻¹. -2 and 0.5 mAh·cm -2 The diagram shows the charge-discharge cycle test conducted under the specified conditions.

[0023] Figure 2 The zinc anode prepared in Comparative Example 6 was tested at 2 mA·cm⁻¹. -2 and 0.5 mAh·cm -2 The diagram shows the charge-discharge cycle test conducted under the specified conditions.

[0024] Figure 3 The zinc anode prepared in Comparative Example 7 was tested at 2 mA·cm⁻¹.-2 and 0.5 mAh·cm -2 The diagram shows the charge-discharge cycle test conducted under the specified conditions.

[0025] Figure 4 The zinc anode prepared in Comparative Example 8 was tested at 2 mA·cm⁻¹. -2 and 0.5 mAh·cm -2 The diagram shows the charge-discharge cycle test conducted under the specified conditions.

[0026] Figure 5 SEM images of zinc anodes prepared in Example 1 and Comparative Example 3, high-resolution SEM images of Example 1 and Comparative Example 1, and elemental mapping of SEM images of Example 1: (a) SEM image of Example 1; (b) SEM image of Comparative Example 3; (cd) High-resolution SEM image of Example 1; (e) EDS image of Example 1.

[0027] Figure 6 AC impedance test diagrams of symmetrical cells assembled with zinc anodes prepared in Example 1 and Comparative Examples 1-3.

[0028] Figure 7 X-ray diffraction patterns of the electrodes prepared in Example 1 and Comparative Example 3.

[0029] Figure 8 Example 1: High-resolution spectrum of Bi 4f obtained by X-ray photoelectron spectroscopy.

[0030] Figure 9 The electrodes prepared in Example 1 and Comparative Example 3 were assembled with Cu electrodes into a half-cell at 1 mA·cm⁻¹ -2 0.5mAh·cm -2 The half-cell cycle diagram was obtained under the following conditions.

[0031] Figure 10 LSV diagrams of the zinc anode three-electrode systems prepared in Example 1 and Comparative Examples 1-3.

[0032] Figure 11 SEM images of the electrodes prepared in Example 1 and Comparative Example 3 after cycling for a period of time. (a) SEM image of Example 1 after cycling; (b) SEM image of Comparative Example 3 after cycling.

[0033] Figure 12 TEM test image of the material in Example 1.

[0034] Figure 13 The electrodes prepared in Example 1 and Comparative Example 3 were assembled with the positive electrode material prepared in Example 5 into a full cell at 0.5 A·g -1 The following is a diagram showing the charge-discharge cycle. Detailed Implementation

[0035] The embodiments of the present invention will be described in detail below with reference to the examples. The following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.

[0036] Example 1 (1) Cleaning of negative electrode material: Zinc foil was placed in an ethanol solution and ultrasonically cleaned for 2 min to obtain a clean zinc foil, which was then cut to a size of 1.13 cm. 2 The zinc discs are cut and then flattened.

[0037] (2) Weigh 1 mmol of bismuth nitrate pentahydrate and 4 mmol of thioacetamide (the molar ratio of bismuth nitrate pentahydrate and thioacetamide is 1:4) using an electronic balance and add them to a 100 ml beaker. Add 50 mL of deionized water and a stir bar of appropriate size. Use a pipette to transfer 5 ml of concentrated hydrochloric acid into the bottle.

[0038] (3) Place the beaker on the stirring table and stir vigorously for 20 min. Then transfer the solution to a 100 mL reaction vessel and react at 140 °C in an oven for 12 h, then cool to ambient temperature. After filtration, a black product (Bi2S3) is obtained, which is washed three times with deionized water and ethanol and dried at 80 °C overnight.

[0039] (4) 0.15 g Bi2S3 and 0.15 g dopamine hydrochloride were ultrasonically dispersed in a trihydroxyaminomethane buffer solution (100 mL, 10 mM) and stirred vigorously for 12 h to allow dopamine hydrochloride to polymerize and coat the surface of Bi2S3 with polydopamine (PDA). The mixture was centrifuged, washed with deionized water and ethanol, and dried at 80 °C for 12 h.

[0040] (5) The above precipitate was calcined at 500°C for 4 h in a nitrogen atmosphere at a heating rate of 2°C / min. PDA carbonization finally yielded Bi2S3@NC material.

[0041] (6) Mix Bi2S3@NC, conductive carbon black and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1, grind and dissolve in N-2-methylpyrrolidone (NMP), coat the slurry onto the zinc foil surface with a 20 µm face of a four-sided coater, and dry in a vacuum drying oven at 80 °C to obtain Bi2S3-NC-20 zinc anode material.

[0042] Example 2 The method and steps are the same as in Example 1, except that the four-sided coating device in step (5) is changed to a 5 µm surface coating to prepare a Bi2S3-NC-5 coated zinc anode.

[0043] Example 3 The method and steps are the same as in Example 1, except that the four-sided coating device in step (5) is changed to a 10 µm surface coating to prepare a Bi2S3-NC-10 coated zinc anode.

[0044] Example 4 The method and steps are the same as in Example 2, except that the four-sided coating device in step (5) is changed to a 50 µm surface coating to prepare a Bi2S3-NC-50 coated zinc anode.

[0045] Comparative Example 1 The method and steps are the same as in Example 1, except step (4) is skipped, and a Bi2S3 coated zinc anode is prepared.

[0046] Comparative Example 2 The method and steps are the same as in Example 1, except that steps (1-3) are skipped and Bi2S3 is not added in step (4) to prepare NC@Zn coated zinc anode.

[0047] Comparative Example 3 The pure zinc negative electrode was cleaned with ethanol and sonicated for 2 minutes to obtain a clean zinc foil, which was then cut into 1.13 cm pieces. 2 Dimensional circular foils are used to obtain Bare Zn electrodes.

[0048] Example 5 The synthesis of the Mn2V2O7 cathode material followed a method reported in previous literature. First, 0.56 g of ammonium metavanadate was added under vigorous stirring, and 0.61 g of oxalic acid dihydrate powder was dissolved in 65 mL of deionized water. Then, 0.94 g of manganese chloride was added to the above mixed solution, and the mixture was stirred for 60 min, followed by the addition of 0.519 g of urea and stirring for 15 min. The solution was then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated at 180 °C for 16 h. Finally, the resulting precipitate was separated by centrifugation, washed with deionized water, and dried at 80 °C to obtain the final Mn2V2O7 sample. Then, the dried Mn2V2O7, conductive carbon black, and PVDF were uniformly mixed in a 7:2:1 mass ratio, and a slurry was prepared using NMP as a solvent. This slurry was then uniformly coated onto a 0.1 mm thick graphite paper surface. The coated cathode material was dried at 80 °C for 12 hours before use. Each positive electrode material was cut into a 1.13 square centimeter disc. All all-electric tests used the positive electrode from Example 5.

[0049] Example 6 Only the amount of hydrochloric acid used in the solvothermal reaction was adjusted, and the rest of the steps were the same as in Example 1. The zinc foil pretreatment was the same as in Example 1. Weigh 1 mmol of bismuth nitrate pentahydrate and 4 mmol of thioacetamide, add 50 mL of deionized water, and add 3 mL of concentrated hydrochloric acid (instead of 5 mL). Stir vigorously for 20 min. The subsequent hydrothermal reaction (140℃ / 12 h), PDA coating, annealing (500℃ / 4 h), and coating (20 μm) steps are the same as in Example 1, to obtain a rod-shaped Bi2S3@NC coated zinc anode with an aspect ratio of 5:1 (the aspect ratio in Example 1 was 10:1). The results are shown in Table 1.

[0050] Example 7 Adjust the ratio of Bi2S3 to dopamine hydrochloride, and follow the same steps as in Example 1; The initial preparation of Bi2S3 was the same as in Example 1; 0.15 g of Bi2S3 and 0.3 g of dopamine hydrochloride (ratio 1:2) were ultrasonically dispersed in trihydroxyaminomethane buffer solution, and subsequent steps remained unchanged to obtain the Bi2S3@NC-1:2 electrode. The results are shown in Table 1.

[0051] Comparative Example 4 Only the morphology of Bi2S3 was changed; the remaining steps were the same as in Example 1. Dissolve bismuth nitrate pentahydrate and thioacetamide (1:4) in 50 mL of deionized water, and add 10 mL of concentrated hydrochloric acid; Spherical Bi2S3 was prepared by hydrothermal reaction at 160℃ for 8 hours; subsequent PDA coating, annealing and coating steps were the same as in Example 1 to obtain spherical Bi2S3@NC electrode.

[0052] Comparative Example 5 The PDA was replaced with a nitrogen-free polymer, and the remaining steps were the same as in Example 1; Bi2S3 was prepared in the same manner as in Example 1; 0.15 g Bi2S3 and 0.15 g polyvinyl alcohol (PVA, nitrogen-free) were ultrasonically dispersed in deionized water and stirred for 12 hours. Bi2S3@nitrogen-free carbon coating was prepared by annealing at 500℃ in a nitrogen atmosphere for 4 hours. The coating process is the same as in Example 1.

[0053] Comparative Example 6 Bi2S3 and NC are directly mixed without PDA coating; Bi2S3 (Steps 1-3 of Example 1) and NC (Step 4 of Example 1, without Bi2S3) were prepared separately. Bi2S3 and NC were physically ground and mixed at a ratio of 1:1, and then mixed with PVDF (7:2) using NMP to form a slurry. The slurry was coated onto zinc foil and dried in the same manner as in Example 1.

[0054] Comparative Example 7 The annealing temperature was changed to 450℃, and the rest was the same as in Example 1.

[0055] Comparative Example 8 The annealing temperature was changed to 650℃, and the rest was the same as in Example 1.

[0056] Analysis and testing: (1) Two zinc anodes prepared in Examples 1 to 4 and two zinc anodes prepared in Comparative Examples 1 to 3 were taken and assembled into symmetrical cells with 2M ZnSO4 electrolyte, glass fiber separator, positive electrode shell, negative electrode shell, gasket and spring sheet, respectively. The cells were then subjected to a 2 mA·cm⁻¹ solution. -2 and 0.5 mAh·cm -2 The test was conducted under the specified conditions, using the LAND battery testing system as the testing software. The test process included constant current discharge followed by charging until the battery was short-circuited or exceeded the protection voltage. The results are as follows: Figure 1 As shown, the BareZn symmetric cell short-circuited after 40 hours of cycling under these conditions; Comparative Example 1 short-circuited after 500 hours of cycling; Comparative Example 2 short-circuited after 1200 hours of cycling; the symmetric cell assembled in Example 2 cycled for 226 hours; the symmetric cell in Example 3 cycled for over 1680 hours before short-circuiting; the symmetric cell assembled in Example 4 cycled for over 245 hours; the symmetric cell assembled in Example 1 had the longest cycle time, at 3200 hours. Unless otherwise specified, subsequent samples refer to the electrodes in Example 1. The results indicate that the material obtained by combining Bi2S3 and NC, due to its unique core-shell structure, effectively enhances its long-cycle capability.

[0057] (2) Two zinc negative electrodes prepared in Comparative Example 6 were taken and assembled into symmetrical cells with 2 M ZnSO4 electrolyte, glass fiber membrane, positive electrode shell, negative electrode shell, gasket, and spring sheet, respectively. The cells were then subjected to a 2 mA·cm⁻¹ temperature range. -2 and 0.5 mAh·cm -2 Charge-discharge cycle tests were conducted under specific conditions. For example... Figure 2 As shown, the symmetrical battery assembled in Comparative Example 6 short-circuited in less than 80 hours, indicating the inadequacy of physical mixing and demonstrating the interfacial advantages of the core-shell structure. (3) The zinc anode assembled symmetrical cell prepared in Comparative Example 7 at 2 mA·cm -2 and 0.5 mAh·cm -2 Charge-discharge cycle tests were conducted under specific conditions. For example... Figure 3 As shown, the symmetrical battery assembled in Comparative Example 7 short-circuited after less than 1000 hours of cycling, indicating that incomplete carbonization is detrimental to the stability of the core-shell structure and cannot support long-term cycling.

[0058] (4) The symmetrical cell assembled with the zinc anode prepared in Comparative Example 8 at 2 mA·cm -2 and 0.5 mAh·cm-2 Charge-discharge cycle tests were conducted under specific conditions. For example... Figure 4 As shown, the symmetrical battery assembled in Comparative Example 8 short-circuited after 180 h of cycling, indicating that excessively high carbonization temperature damaged the stability of the core-shell structure and was detrimental to cycle performance.

[0059] (5) SEM tests were performed on Example 1 and Comparative Examples 1 and 3. SEM images of the bare zinc showed significant unevenness on the surface. This unevenness led to a non-uniform electric field distribution during charging and discharging, ultimately resulting in non-uniform zinc deposition on the electrode surface. SEM images of the Bi2S3-NC@Zn sample showed that the Bi2S3-NC coating was uniformly applied to the zinc substrate. High-resolution SEM images of Bi2S3-NC and Bi2S3 also indicated that Bi2S3 has a rod-like structure, while NC uniformly coats Bi2S3, forming a core-shell structure. EDS elemental mapping results showed the presence of Bi, N, C, and S elements, preliminarily proving that the Bi2S3-NC coating was successfully prepared and uniformly distributed on the zinc electrode surface.

[0060] (6) Two zinc anodes prepared in Example 1 and Comparative Examples 1-3 were taken and assembled into symmetrical cells with 2 M ZnSO4 electrolyte, glass fiber separator, positive electrode shell, negative electrode shell, gasket, and spring sheet, respectively. Testing was performed on the Chenhua electrochemical workstation. AC impedance testing was selected, with the initial voltage set to open circuit voltage and a frequency range of 10 Hz. -1 ~10 5 Hz. The result is as follows: Figure 6 As shown, the charge transfer impedance of the Bi2S3@NC assembled battery is only 33.23 Ω, far less than the 129.4 Ω of the bare zinc assembled battery. Meanwhile, the charge transfer impedance of the Bi2S3@Zn assembled battery is 41.37 Ω, and that of the NC@Zn assembled battery is 81.86 Ω. This indicates that the Bi2S3@NC coating can effectively enhance the charge transfer capability at the electrode / electrolyte interface and improve the reaction kinetics of the electrochemical reaction during zinc deposition / stripping. Furthermore, while Bi2S3 and NC alone can also enhance charge transfer capability, the core-shell structure formed by their combination further amplifies this advantage.

[0061] (7) X-ray diffraction tests were performed on the electrodes prepared in Example 1 and Comparative Examples 1-3, with a test range of 5~80°. The results are as follows: Figure 7 As shown. By comparing with the standard card (PDF#17-1864), it is demonstrated that the coating on the sample surface is mainly composed of Bi2S3 and that the introduction of the coating does not disrupt the crystal structure of zinc. Furthermore, nitrogen-doped carbon materials do not affect the crystal structure of Bi2S3 or zinc.

[0062] (8) The electrode prepared in Example 1 was subjected to X-ray photoelectron spectroscopy, and the results are as follows: Figure 8 As shown in the high-resolution photoelectron spectroscopy (HPS) of Bi₂S₃, the peaks at 158.62 eV and 163.82 eV correspond to Bi₄f. 3+ In the high-resolution XPS spectra of Bi₂S₃-NC for Bi₄f and S₂p, two pairs of peaks can be observed, located at 158.44 / 163.76 eV and 161.03 / 162.40 eV, respectively. These peaks typically correspond to Bi₄f in the Bi₂S₃ phase. 5 / 2 / 4f 7 / 2 and S 2p 1 / 2 / 2p 3 / 2 Furthermore, the weak peaks at 159.07 / 164.41 eV of Bi₄f may be due to the presence of Bi-OC bonds. The presence of the Bi-OC structure indicates a strong interfacial interaction between Bi₂S₃ and nitrogen-doped carbon. This oxygen-bridging interface not only facilitates ion and electron transport between Bi₂S₃ and nitrogen-doped carbon, but also effectively prevents the stripping of Bi₂S₃ from nitrogen-doped carbon during charge and discharge.

[0063] (9) The electrodes prepared in Example 1 and Comparative Example 3 were assembled with Cu electrodes to form a half-cell, and the temperature was measured at 1 mA·cm⁻¹. -2 0.5 mAh·cm -2 Under certain conditions, half-cell cycling was performed using the LAND battery testing system. The test process involved constant current discharge followed by charging until the battery short-circuited or exceeded the protection voltage. The results are as follows: Figure 9 As shown, the Bare Zn / / Cu half-cell exhibited a short circuit after 100 cycles and its coulombic efficiency was unstable; while the Bi2S3@NC / / Cu half-cell cycled for more than 270 cycles and had a more stable coulombic efficiency, indicating that the Bi2S3@NC coating can significantly improve the deposition and stripping ability of zinc and improve the stability of the zinc anode.

[0064] (10) The zinc anodes prepared in Example 1 and Comparative Examples 1-3 were used as working electrodes, and three-electrode systems were tested with 2 M NaSO4 electrolyte, Pt electrode, and AgCl reference electrode, respectively. The tests were performed on a Chenhua electrochemical workstation. LSV testing was selected, with a voltage window of -0.6 to -2.4 V. The results are as follows: Figure 10As shown, the Bi2S3@NC electrode exhibits the best resistance to hydrogen evolution. Meanwhile, the Bi2S3@Zn electrode and the NC@Zn electrode also show better resistance to hydrogen evolution than pure zinc, but the performance is further enhanced after the composite formation. This indicates that the Bi2S3@NC coating can effectively enhance the charge transfer capability at the electrode / electrolyte interface and improve the reaction kinetics of the electrochemical reaction during zinc deposition / stripping. Furthermore, while Bi2S3 and NC alone can enhance resistance to hydrogen evolution, the core-shell structure formed by their composite structure further amplifies this advantage.

[0065] (11) The electrodes prepared in Example 1 and Comparative Example 3 were subjected to a current density of 5 mA·cm⁻¹. -2 and 1 mAh·cm -2 The surface morphology was tested after 20 hours of the next cycle, and the results are as follows: Figure 11 As shown, the surface of the cycled pure zinc electrode exhibits numerous disordered and large dendrites. In contrast, the surface of the cycled Bi2S3-NC@Zn electrode is smooth, showing uniform zinc deposition. This makes it less likely for the diaphragm to be punctured, causing a short circuit in the battery. This result effectively demonstrates the role of the Bi2S3-NC coating in inhibiting dendrite growth.

[0066] (12) The material prepared in Example 1 was subjected to TEM testing, and the results are as follows: Figure 12 As shown, rod-shaped Bi2S3 atoms are clearly visible in the TEM image of the Bi2S3-NC material, with carbon material coating the Bi2S3 atoms, together forming a core-shell structure of the Bi2S3-NC composite material. Elemental mapping images further confirm this, showing that Bi and S elements are concentrated in the central rod-shaped region, while C and N elements are dispersed around the rod-shaped structure.

[0067] (13) The electrodes prepared in Example 1 and Comparative Example 3 were assembled with the positive electrode material prepared in Example 5 to form a full cell at 0.5 A·g -1 The battery underwent charge-discharge cycles using the LAND battery testing system. The testing process involved constant current discharge followed by charging until the battery short-circuited or exceeded its protection voltage. The results are as follows: Figure 13 As shown, the results indicate that after 1400 cycles, the Bi2S3-NC@Zn assembled battery still retains 115.7 mAh g⁻¹. -1 The specific capacity is higher, while pure zinc only has 64.3 mAh g. -1 The capacity indicates that the Bi2S3-NC@Zn electrode can enhance the capacity and cycle stability of the full cell.

[0068] (14) Full cells were assembled from Examples 6-7 and Comparative Examples 4-5. The results are shown in Table 1. After 200 cycles, the capacity retention of the full cell assembled in Comparative Example 4 was only 44.39%; after 210 cycles, the capacity retention of the full cell assembled in Comparative Example 5 was only 46.18%; after 1000 cycles, the capacity retention of the full cell assembled in Example 6 was only 51.4%; and after 205 cycles, the capacity retention of the full cell assembled in Example 7 was only 51.5%. These results demonstrate the superior performance of the rod-shaped core-shell structure and the necessity of a 1:1 ratio of bismuth sulfide to PDA and a 1:5 aspect ratio of bismuth sulfide.

[0069] Table 1

[0070] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all fall within the protection scope of the present invention.

Claims

1. A zinc anode modified with a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer, characterized in that, It includes a zinc substrate and a bismuth sulfide-nitrogen-doped carbon interface modification layer coated on its surface.

2. A method for preparing a zinc anode modified with a rod-shaped bismuth sulfide-nitrogen-doped carbon composite interface layer, characterized in that, Includes the following steps: (1) Add bismuth nitrate pentahydrate and thioacetamide to deionized water, and then add concentrated hydrochloric acid to obtain a mixed solution; (2) After stirring the mixed solution, the reaction was carried out. After filtration, a black product was obtained. It was washed with deionized water and ethanol once, dried, and then cooled to ambient temperature to obtain Bi2S3. (3) Bi2S3 and dopamine hydrochloride were ultrasonically dispersed in a trihydroxyaminomethane buffer solution, allowing dopamine hydrochloride to polymerize and coat the surface of Bi2S3 with polydopamine. The mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain the precipitate. (4) The above precipitate was calcined in a nitrogen atmosphere to finally obtain Bi2S3@NC material; (5) Mix and grind Bi2S3@NC, conductive carbon black and polyvinylidene fluoride and dissolve them in N-2-methylpyrrolidone. Use a four-sided coater to coat the slurry onto the surface of zinc foil. After drying, the modified zinc anode material can be obtained.

3. The preparation method according to claim 2, characterized in that, In step (1), the molar ratio of bismuth nitrate pentahydrate to thioacetamide is 1:(3-5), preferably 1:4, and the molar volume of bismuth nitrate pentahydrate, thioacetamide, deionized water, and concentrated hydrochloric acid is 1:(3-5):(40-60):(4-6) mmol / mmol / mL / mL, preferably 1:4:50:5 mmol / mmol / mL / mL.

4. The preparation method according to claim 2, characterized in that, In step (2), the stirring is performed for 15-25 minutes at a speed of 480-600 rpm; preferably, the stirring is performed for 20 minutes at a speed of 500 rpm.

5. The preparation method according to claim 2, characterized in that, In step (2), the reaction conditions are 130-150℃ for 10-14h, preferably 140℃ for 12h.

6. The preparation method according to claim 2, characterized in that, In step (3), the solid-liquid ratio of Bi2S3 and dopamine hydrochloride to trihydroxyaminomethane buffer solution is 1:1:(90-110) g / g / mL, preferably 1:1:100 g / g / mL, the concentration of trihydroxyaminomethane buffer solution is 8-12 mM, the ultrasonic dispersion conditions are 35-45 kHz, and the dispersion time is 10-15 h, preferably the concentration of trihydroxyaminomethane buffer solution is 10 mM, the ultrasonic dispersion conditions are 40 kHz, and the dispersion time is 12 h. In steps (2), (3), and (5), the drying conditions are vacuum drying at 75-90℃ for 10-14 hours, preferably vacuum drying at 80℃ for 12 hours.

7. The preparation method according to claim 2, characterized in that, In step (4), the calcination temperature is 480-600℃, the calcination time is 3-5 h, and the heating rate is 1-3℃ / min; preferably, the calcination temperature is 500℃, the calcination time is 4 h, and the heating rate is 2℃ / min. In step (5), Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride are mixed, ground, and dissolved in N-2-methylpyrrolidone. The mass ratio of Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride is (5-8):(1-3):

1. Preferably, the mass ratio of Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride is 7:2:

1. The concentration of the mixture of Bi2S3@NC, conductive carbon black, and polyvinylidene fluoride in N-2-methylpyrrolidone is 0.4-0.7 g / mL, preferably 0.5 g / mL.

8. The preparation method according to claim 2, characterized in that, In step (5), the coating thickness of the four-sided coater is 5-50µm, preferably 20µm; The zinc foil mentioned in step (5) is a pre-treated zinc foil. The zinc foil pre-treatment steps are: placing the zinc foil in an organic solvent for ultrasonic cleaning, and then cutting and flattening the zinc foil; The organic solvent is ethanol or NMP, with a mass percentage ≥95%; the zinc foil is cut into round pieces.

9. The application of a zinc anode composed of bismuth sulfide-nitrogen-doped carbon material as described in claim 1, or a zinc anode composed of bismuth sulfide-carbon material prepared by any one of claims 2 to 8, characterized in that, It is used as a negative electrode material in aqueous zinc-ion batteries.

10. An aqueous zinc-ion battery, characterized in that, The zinc anode of claim 1 or the zinc anode prepared by any one of claims 2 to 8 is used as the anode, the cathode material is Mn2V2O7, the electrolyte is an aqueous solution of zinc salt, and the separator is glass fiber.